Warfare, Political Economy, and Social Formations: Considering Central Andean Prehistory - Earle, Timothy (2023)
Warfare is critical for anthropologists and prehistorians studying variation in human economies and societies. To view this variable comparatively, we must consider severity and regularity as documented by defensive facilities and locations, nature and frequency of weaponry, and bodily injuries likely from combat. Arkush (2022 and companion article) provides detailed documentation for explaining Andean warfare. Here, I look at war- fare as a constellations of phenomena involving raiding for wealth, competition over cor porate land ownership, and conquest warfare by complex chiefdoms and states aimed at maximizing the extraction of surpluses. My goal is to model warfare as imbedded within political economies with different goals and means based on sources of economic power. This is fundamentally a Marxist orientation, considering contrasting modes of economic organization representing competitive processes between interest groups. The Andean data suggest that warfare was elementally competition for corporately held agricultural lands intensified by facilities including especially irrigation. It varied in frequency and severity with population density increasing through time. With the emergence of institutional finance, however, overarching polities focus on conquest and intimidation to maximize surplus extraction as they imposed regional peace as documented for example by coastal EIP states and the Inca empire. Elaboration of offensive weaponry did not characterize Andean sequences in sharp contrast to Bronze and Iron Age Europe, suggesting distinctive trajectories of warfare. Key for success in Andean warfare was sizes of fighting forces as characterized by the numbers of sandals on the ground.